2006
DOI: 10.1177/00222194060390020401
|View full text |Cite
|
Sign up to set email alerts
|

Response to Intervention as a Vehicle for Distinguishing Between Children With and Without Reading Disabilities

Abstract: Children at risk for early reading difficulties were identified on entry into kindergarten, and half of these children received small-group intervention two to three times a week during their kindergarten year. The other half received whatever remedial assistance was offered by their home schools. These children were again assessed at the beginning of first grade, and those who continued to have difficulties in reading received either one-to-one daily tutoring offered by project teachers from the beginning to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
184
2
10

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(211 citation statements)
references
References 12 publications
10
184
2
10
Order By: Relevance
“…Although student outcomes continued to improve with each intervention, the identified growth groups remained distinct on outcome measures after the second intervention. In a subsequent study (Vellutino, Scanlon, Small, & Fanuele, 2006), kindergarten students at risk for reading problems were provided an intervention using a standard protocol. When compared to students at risk and who received no kindergarten intervention, the intervention group had better performance on a range of reading measures.…”
Section: Standard Protocolsmentioning
confidence: 99%
“…Although student outcomes continued to improve with each intervention, the identified growth groups remained distinct on outcome measures after the second intervention. In a subsequent study (Vellutino, Scanlon, Small, & Fanuele, 2006), kindergarten students at risk for reading problems were provided an intervention using a standard protocol. When compared to students at risk and who received no kindergarten intervention, the intervention group had better performance on a range of reading measures.…”
Section: Standard Protocolsmentioning
confidence: 99%
“…These researchers encourage the continuation of identification and classification based on discrepancies between achievement and ability, with ability defined by scores on multiple cognitive processing tests rather than a single IQ test (Hale, Naglieri, Kaufman, & Kavale, 2004). However, many other researchers see RtI as a prevention model that stimulates multiple tiers of intervention and reduces the possibility that students referred to special education are academic casualties from inadequate or inappropriate instruction (Fletcher, Coulter, Reschly, & Vaughn, 2004 Otaiba & Fuchs, 2006;Mathes et al, 2005;McMaster, Fuchs, Fuchs, & Compton, 2005;Vaughn, Linan-Thompson, & Hickman, 2003;Vellutino et al, 1996;Vellutino, Scanlon, Small, & Fanuele, 2006). A synthesis of recent research on intensive, early interventions reveals higher effects for smaller group size and for an earlier start of intervention (e.g., kindergarten-grade 1; Wanzek & Vaughn, 2006).…”
Section: Predicting Reading Difficulties In Young Childrenmentioning
confidence: 99%
“…This is despite formal UK educational policy guidelines, which state that ‘dyslexia’ occurs across the range of intellectual abilities, is best thought of as a continuum, and has no clear cutoff points (Rose, 2009). The discrepancy model's gradual decline in education, as opposed to research, has come about largely because all poor readers have been shown to benefit from similar intervention, at least in the early stages (Vellutino, Scanlon, Small, & Fanuele, 2006). …”
Section: Introductionmentioning
confidence: 99%